Outer measures on a commutative ring induced by measures on its spectrum - Dudzik, Dariusz; Skrzyński, Marcin (Annales Mathematicae Silesianae, 2017)
On a commutative ring R we study outer measures induced by measures on Spec(R). The focus is on examples of such outer measures and on subsets of R that satisfy the Carathéodory condition.